Production of high specific activity 195mPt-cisplatinum at South African Nuclear Energy Corporation for Phase 0 clinical trials in healthy individual subjects - Zeevaart, Jan Rijn; Wagener, Judith; Marjanovic-Painter, Biljana; Sathekge, Mike; Soni, Nischal; Zinn, Christa; Perkins, Gary; Smith, Suzanne V. (Journal of labelled compounds & radiopharmaceuticals, 2013)
Platinum agents continue to be the main chemotherapeutic agents used in the first‐line and second‐line treatments of cancer patients. It is important to fully understand the biological profile of these compounds in order to optimize the dose given to each patient. In a joint project with the Australian Nuclear Science and Technology Organisation and the Nuclear Medicine Department at Steve Biko Academic Hospital, South African Nuclear Energy Corporation synthesized and supplied 195mPt‐cisplatinum (commonly referred to as cisplatin) for a clinical pilot study on healthy volunteers. Enriched 194PtCl2 was prepared by digestion of enriched 194Pt metal (>95%) followed by thermal decomposition over a 3 h period. The 194PtCl2 was then placed in a quartz ampoule, was irradiated in SAFARI‐1 up to 200 h, then decay cooled for a minimum of 34 h prior to synthesis of final product. 195mPt(NH3)2I2, formed with the addition of KI and NH4OH, was converted to the diaqua species [195mPt(NH3)2(H2O)2]2+ by reaction with AgNO3. The conversion to 195mPt‐cisplatinum was completed by the addition of concentrated HCl. The final product yield was 51.7% ± 5.2% (n = 5). The chemical and radionuclidic purity in each case was >95%. The use of a high flux reactor position affords a higher specific activity product (15.9 ± 2.5 MBq/mg at end of synthesis) than previously found (5 MBq/mg). Volunteers received between 108 and 126 MBq of radioactivity, which is equivalent to 6.8–10.0 mg of carrier cisplatinum. Such high specific activities afforded a significant reduction (~50%) in the chemical dose of a carrier cisplatinum, which represents less than 10% of a typical chemotherapeutic dose given to patients. A good manufacturing practice GMP compliant product was produced and was administered to 10 healthy volunteers as part of an ethically approved Phase 0 clinical trial. The majority of the injected activity 27.5% ± 5.8% was excreted in the urine within 5 h post injection (p.i.). Only 8.5% ± 3.1% of cisplatinum remained in blood pools at 5 h, which gradually cleared over the 6‐day monitoring period p.i. At the end of the study (6 days p.i.), a total of 37.4% ± 5.3% of the product had cleared from the blood into urine, and approximately 63% remained in the body. The significantly lower concentration of carrier cisplatinum used for imaging resulted in a well‐tolerated product. Copyright © 2013 John Wiley & Sons, Ltd. Platinum continue to be the main chemotherapeutic agents used in the first‐line and second‐line treatments of cancer patients. It is important to fully understand the biological profile of these compounds in order to optimize the dose given to each patient. 195mPt‐cisplatinum (commonly referred to as cisplatin) was produced from 194PtCl2 that was irradiated in SAFARI‐1 for up to 200 h. The final product yield was 51.7% ± 5.2%, and the chemical and radionuclidic purity for each production run passed the quality control providing a good manufacturing practice compliant product that was administered to 10 healthy volunteers as part of an ethical approval Phase 0 clinical trial. Volunteers received between 108 and 126 MBq of radioactivity and 6.8–10 mg of carrier cisplatinum, which was well‐tolerated. The majority of the injected activity 27.5% ± 5.8% was excreted in the urine within 5 h post injection (p.i.). Only 8. 5% ± 3.1% of cisplatinum remained in blood pools at 5 h, which gradually cleared over the 6‐day monitoring period p.i. At the end of the study (6 days p.i.), a total of 37.4% ± 5.3% of the product had cleared from the blood into urine, meaning that around 63% remained in the body.